Effects of Fermentation on Standardized Ileal Digestibility of Amino Acids and Apparent Metabolizable Energy in Rapeseed Meal Fed to Broiler Chickens - Wu, Zhengke (Animals (Basel), 2020)
SIMPLE SUMMARY: Rapeseed meal (RSM) is a by-product of rapeseed oil production. Owing to its lower cost and abundant sulfur-containing amino acids, RSM can be used for replacing soybean meal in broiler diets. However, its use is limited by the presence of numerous anti-nutritional factors. As an ancient technique to convert the complex substrates into simple compounds by a number of microorganisms, microbial solid-state fermentation (SSF) has been shown as an effective way to eliminate or reduce anti-nutritional factors in RSM and improve growth performance when fed to animals. This improvement is not yet clear; in particular, the understanding of the feeding nutritional value of fermented rapeseed meal (FRSM) is not very well studied. Hence, the trial is conducted to investigate the effects of fermentation on standardized ileal digestibility (SID) of amino acids and apparent metabolizable energy (AME) in RSM fed to broiler chickens. According to our findings, fermentation had a significant effect on the chemical composition of RSM. In comparison to RSM, FRSM had greater nitrogen-corrected apparent metabolizable energy (AMEn) values and SID of amino acids. FRSM was nutritionally superior to RSM for use in broiler diets. ABSTRACT: Rapeseed meal (RSM) is a common protein ingredient in animal diets, while the proportion of RSM in diets is limited because of its anti-nutritional factors. Fermentation based on mixed microbial strains appears to be a suitable approach to improve the nutritive value of rapeseed meal in animal feed. In this study, we evaluated the effects of fermentation on the apparent metabolizable energy (AME) values and standardized ileal digestibility (SID) of amino acids in RSM fed broilers. The AME and nitrogen-corrected apparent metabolizable energy (AMEn) values of RSM and fermented rapeseed meal (FRSM) were determined by the substitution method, with RSM and FRSM proportionally replacing the energy-yielding components of the basal diet by 30%. Results show that fermentation improved AME and AMEn of RSM from 7.44 to 8.51 MJ/kg and from 7.17 to 8.26 MJ/kg, respectively. In the second experiment, two experimental diets were formulated, with RSM and FRSM being the sole sources of amino acids. A nitrogen-free diet (NFD) was also formulated to determine endogenous amino acids losses (EAAL). Feeding on FRSM resulted in higher (p < 0.05) apparent ileal digestibility (AID) and SID of alanine, valine, isoleucine, leucine, tyrosine, lysine, arginine, and phenylalanine. No significant differences between RSM and FRSM were found for AID and SID of asparagine, histidine, threonine, serine, glutamine, praline, glycine, methionine, and cystine. FRSM had greater AMEn values and SID of amino acids compared to RSM, therefore, FRSM was nutritionally superior to RSM in broiler diets.